2021
DOI: 10.1002/tea.21739
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐service teachers enactment of language‐ and literacy‐integrated science instruction in linguistically diverse science classrooms

Abstract: The Next Generation Science Standards and increasing linguistic diversity of students in United States science classrooms require language‐focused science instruction for which many secondary science teachers are not prepared. To date, minimal research has addressed how to best support secondary science pre‐service teachers (PSTs) in teaching in linguistically diverse classrooms despite the fact that most PSTs will have the opportunity to teach emergent bilinguals (EBs) at some point in their careers. The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…While results on the extent to which PSTs implemented the TELLIS practices in their student teaching placements, and in what ways they did so, are detailed in another manuscript (see Rutt & Mumba, 2021a), overall analyses revealed that all three PSTs were able to enact most TELLIS practices at the targeted Implementing level (or higher) at least once over the course of their four‐lesson units, with average implementation falling at the mid‐ to high‐ Beginning level for most practices (see Table 3). Differences were identified among PSTs' level of enactment for some practices.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While results on the extent to which PSTs implemented the TELLIS practices in their student teaching placements, and in what ways they did so, are detailed in another manuscript (see Rutt & Mumba, 2021a), overall analyses revealed that all three PSTs were able to enact most TELLIS practices at the targeted Implementing level (or higher) at least once over the course of their four‐lesson units, with average implementation falling at the mid‐ to high‐ Beginning level for most practices (see Table 3). Differences were identified among PSTs' level of enactment for some practices.…”
Section: Resultsmentioning
confidence: 99%
“…Particular attention was given to the collective affordances and constraints that the mediating elements of the activity systems provided in PSTs' attempts to obtain the object of their activity systems (i.e., LLIS instruction, as operationalized by the TELLIS framework, at the Implementing level or above). While results on the extent to which PSTs implemented the TELLIS practices in their student teaching placements, and in what ways they did so, are detailed in another manuscript (see Rutt & Mumba, 2021a), overall analyses revealed that all three PSTs were able to enact most TELLIS practices at the targeted Implementing level (or higher) at least once over the course of their four-lesson units, with average implementation falling at the mid-to high-Beginning level for most practices (see Table 3). Differences were identified among PSTs' level of enactment for some practices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, MLs participate meaningfully by deploying multiple modalities, including gesture (e.g., Ünsal et al, 2018), visual representation (e.g., Ryoo & Bedell, 2018), and embodied representation (e.g., Varelas et al, 2022); multiple registers of language, including both everyday and specialized registers (e.g., Brown & Ryoo, 2008; Cardozo‐Gaibisso et al, 2020); and multiple named languages, such as Spanish and English (e.g., Rutt & Mumba, 2022; Suárez, 2020)—all in the context of goal‐directed interactions with peers (e.g., González‐Howard & McNeill, 2016) and artifacts in their environment (e.g., Ryoo & Bedell, 2018). This shift from a deficit‐oriented to asset‐oriented view of MLs is evident in the evolving terminology used to refer to these students (González‐Howard & Suárez, 2021; Grapin, 2021; WIDA Consortium, 2020), from “English learner,” which emphasizes what students are perceived to be lacking (i.e., English), to “multilingual learner,” which emphasizes what resources they bring (i.e., multiple and varied meaning‐making resources).…”
Section: Literature Reviewmentioning
confidence: 99%